Novel 5‐point 18‐FDG‐PET/CT visual scoring system for assessing treatment response in patients with oesophageal or gastro‐oesophageal junction carcinoma. Issue 1 (15th October 2020) - Cong, Edward; Oar, Andrew J; Lee, Mark T; Chicco, Andrew; Lin, Michael; Yap, June; Lin, Peter; Ho Shon, Ivan
Abstract: Introduction: The purpose of this study was to investigate the prognostic utility and reproducibility of a qualitative 5‐point 18‐fluorodeoxyglucose (FDG)‐PET primary visual score (PVS) in patients with oesophageal and gastro‐oesophageal junction (GOJ) cancer. Methods: This was a retrospective review of patients with histologically proven oesophageal or GOJ cancer who received curative intent therapy. Clinical, pathological and imaging data were extracted from electronic medical records. Patients were required to have pre‐treatment and post‐treatment FDG‐PET scans, that were evaluated with a 5‐point primary visual score (prePVS, postPVS). The changes in PVS (ΔPVS) were correlated with progression‐free survival and overall survival. Interobserver variability was assessed using Cohen's Kappa intraclass correlation and agreement. Results: Sixty‐seven patients were retrospectively identified. Two (3%), 36 (54%) and 29 (43%) of the patients had stage I, II and III disease respectively. Twenty‐five (37%) patients had squamous cell carcinoma. Thirty‐seven (55%) patients proceeded onto surgical resection. postPVS was associated with both PFS ( P  = 0.013) and OS ( P  = 0.0002). ΔPVS predicted for PFS ( P  = 0.002) and OS ( P  = 0.0003). When thresholds of response were considered, agreement was 80.6% ( K  = 0.78) and 74.6% ( K  = 0.69) for postPVS and ΔPVS respectively. Conclusion: Qualitative assessment of oesophageal and GOJ cancers utilising FDG‐PET is reproducible and may be able to prognosticate outcomes in patients undergoing treatment. Prospective validation is required.